TERRA, hnRNP A1, and DNA-PKcs Interactions at Human Telomeres - Le, Phuong N.; Maranon, David G.; Altina, Noeila H.; Battaglia, Christine L.; Bailey, Susan M. (Frontiers in Oncology, 2013)
Maintenance of telomeres, repetitive elements at eukaryotic chromosomal termini, and the end-capping structure and function they provide, are imperative for preserving genome integrity and stability. The discovery that telomeres are transcribed into telomere repeat containing RNA (TERRA) has revolutionized our view of this repetitive, rather unappreciated region of the genome. We have previously shown that the non-homologous end-joining, shelterin associated DNA dependent protein kinase catalytic subunit (DNA-PKcs) participates in mammalian telomeric end-capping, exclusively at telomeres created by leading-strand synthesis. Here, we explore potential roles of DNA-PKcs and its phosphorylation target heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) in the localization of TERRA at human telomeres. Evaluation of co-localized foci utilizing RNA-FISH and three-dimensional (3D) reconstruction strategies provided evidence that both inhibition of DNA-PKcs kinase activity and siRNA depletion of hnRNP A1 result in accumulation of TERRA at individual telomeres; depletion of hnRNP A1 also resulted in increased frequencies of fragile telomeres. These observations are consistent with previous demonstrations that decreased levels of the nonsense RNA-mediated decay factors SMG1 and UPF1 increase TERRA at telomeres and interfere with replication of leading-strand telomeres. We propose that hTR mediated stimulation of DNA-PKcs and subsequent phosphorylation of hnRNP A1 influences the cell cycle dependent distribution of TERRA at telomeres by contributing to the removal of TERRA from telomeres, an action important for progression of S-phase, and thereby facilitating efficient telomere replication and end-capping.